Estudio de Mercado para los productores de maíz; pequeños, medianos y grandes en el sector de Celica, Pindal y Zapotillo, periodo 2021. - Jazmín Irene, Barriga Salinas (2023)
The Degree Project called "MARKET STUDY FOR MAIZE PRODUCERS; SMALL, MEDIUM AND LARGE IN THE SECTOR OF CELICA, PINDAL AND ZAPOTILLO, PERIOD 2021. "This study has been developed according to the Academic Regulations of the National University of Loja, as a requirement to obtain the degree and title of Engineer in Accounting and Auditing, Public Accountant-Auditor, which allows the fulfillment of the objectives set by the execution of the work and in turn provides a contribution to all producers for the improvement of the production of hard corn in Celica, Pindal and Zapotillo. To begin with the fulfillment of the objectives of the market study, a visit was made to each sector where the study was to be carried out, which were Celica, Pindal and Zapotillo, a sample of 113 producers was taken, including large, A sample of 113 producers between large, medium and small producers of the three sectors was taken, to which a survey was applied to collect the necessary information and establish the value chain for which we asked about the centers of activity performed during the entire production being these the planting, cultural work and harvesting of each center activities such as planting and land preparation, spraying, harvesting, piling, shelling and finally having the realization of the sale are broken down; This allowed us to fulfill the first objective which is to find the market niche of the producers and in turn determined the supply and demand of the three sectors, to meet our next objectives an interview was conducted to collect data such as raw materials, direct and indirect labor, inputs, expenses and costs required in all production, which allowed us to find the break-even point according to their costs and the relationship of the same. Finally, after collecting all this information it is known that the three types of producers have a good profitability, having the knowledge of their costs and expenses, in addition to the sales that they make, their profitability is sufficient to pay debts such as loans to banks and to subsist day to day until starting again with the production, In case there are other types of scenarios, such as the optimistic one in the case that the state helps producers with subsidies or the pessimistic one if the price of fuel continues to rise, the profitability would change, being the optimistic scenario the one that benefits the producer the most, since he would reduce certain expenses and his profits would be better.